On humour - Critchley, Simon 1960- (Routledge, 2002)
Simon Critchley skillfully probes some of the most perennial but least understood features of humour, such as our tendency to laugh at animals and our bodies, why we mock death with comedy and why we think it's funny when people act like machines.
Keywords: Filosofische aspecten; Humor (grappigheden); Humour - Histoire et critique; Philosophie; Wit and humor -- History and criticism; Humor; Literatur